1996
DOI: 10.1046/j.1365-3083.1996.d01-322.x
|View full text |Cite
|
Sign up to set email alerts
|

Primitive Cytokines and Cytokine Receptors in Invertebrates: the Sea Star Asterias rubens as a Model of Study

Abstract: It has been previously demonstrated that the sea star axial organ is a primitive immune organ. Phagocytic, lymphoid-like cells have been characterized with properties similar to those of vertebrates. There is also evidence for an invertebrate cytokine network because IL-1 and TNF-like activities are clearly demonstrable. In addition, the authors have previously described preliminary evidence for IL-2-like activity in the sea star. In the present report, the authors obtained evidence for the presence of IL-1- a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 7 publications
0
14
0
2
Order By: Relevance
“…In mice, receptors are also expressed in germinal and somatic compartments of the testis, but receptor ablation is only dispensable in the germ cell compartment, while Sertoli cellspecific loss of the IGF receptor (or of IGF and insulin receptors), compromised Sertoli cell proliferation and hence adult testis size and sperm output (56). Also in trout (57) and seabream (58), Igf receptors were found in somatic and germ cells, which is consistent with our analysis of Igf receptor gene expression in wild-type and germ cellfree mutant zebrafish. Genetic evidence as regards the cell type-specific effects of receptor gene ablation is missing in zebrafish, but recent work showed that thyroid hormoneinduced Sertoli cell proliferation involved elevated igf3 transcript levels, and that this proliferation was compromised (but not fully blocked) by an Igf receptor antagonist (59).…”
Section: Discussionmentioning
confidence: 99%
“…In mice, receptors are also expressed in germinal and somatic compartments of the testis, but receptor ablation is only dispensable in the germ cell compartment, while Sertoli cellspecific loss of the IGF receptor (or of IGF and insulin receptors), compromised Sertoli cell proliferation and hence adult testis size and sperm output (56). Also in trout (57) and seabream (58), Igf receptors were found in somatic and germ cells, which is consistent with our analysis of Igf receptor gene expression in wild-type and germ cellfree mutant zebrafish. Genetic evidence as regards the cell type-specific effects of receptor gene ablation is missing in zebrafish, but recent work showed that thyroid hormoneinduced Sertoli cell proliferation involved elevated igf3 transcript levels, and that this proliferation was compromised (but not fully blocked) by an Igf receptor antagonist (59).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of endogenous immunomodulatory molecules has been indirectly demonstrated in various invertebrate taxa such as molluscs, anellids, echinoderms and tunicates (Ottaviani et al, 1995a(Ottaviani et al, ,b, 1997a(Ottaviani et al, ,b, 2000(Ottaviani et al, , 2004De Eguileor et al, 2004;Beck andHabicht, 1986, 1991;Legac et al, 1996;Raftos, 1996;Terajima et al, 2003), although the occurrence of molecules sharing homologies with vertebrate cytokines is still a matter of debate (Beck, 1998;Beschin et al, 2001Beschin et al, , 2004.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, molecules cross-reacting with antibodies elicited against the chemokine IL-8 and against transforming growth factor (TGF)-b1, two other vertebrate cytokines involved in inflammatory processes and produced by macrophages [38,39] have been identified in molluscs. Furthermore, IL-2-like activity was detected in protochordates and echinoderms, that is in deuterostome invertebrates having a hematopoietic organ and T-like cells [12,29]. Searches for homologies at the genome level also suggest the existence of cytokine-like molecules in invertebrates.…”
Section: Evidence For the Existence Of Invertebrate Cytokine-like Facmentioning
confidence: 99%
“…In this regard, Legac et al reported the cross-reaction of antibodies elicited against human IL-1, IL-6, IL-2 and IFN-g receptors with surface molecules on cells from the echinoderm hematopoietic axial organ [29]. In addition, human IL-1 (huIL-1) was documented to bind specifically to the coelomocyte membrane of echinoderms, whereas huIL-2 was shown to enhance the cell proliferation in protochordate pharyngeal explants [14,34,46].…”
Section: Evidence For the Existence Of Invertebrate Cytokine Receptormentioning
confidence: 99%